Antioxidantes en las plantas aromáticas y medicinales una opción en la salud humana. - Díaz Pérez, Tomás; Alcántara Rodríguez, Pedro; Salgado Pulido, Julia Mirta; Rodriguez Lugo, Barbara Gudelia (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2024)
Antioxidants are molecules found in living beings (cells, plants, animals and man), responsible for retarding the oxidation of other molecules, in the aging process over the years and this degeneration is carried out through oxidation. At present, interest in new natural sources of antioxidants has increased due to two main reasons: the first is that they have proven beneficial effects on health, since they counteract the action of free radicals; the second is that some synthetic antioxidants used in the food industry that have toxic effects, accumulate in fatty tissue and have been shown to be carcinogenic. Its objective is to identify the antioxidants of the 28 aromatic and medicinal species existing in the institute with a view to strengthening the quality of life, nutritional contribution, empowering their eating habits and consumption. The bibliographic report method, generic method, was used. In this review, the types of Hydrophilic (Water Soluble), Hydrophobic (Fat Soluble) and other types of antioxidants such as polyphenols were characterized and among them are Flavonoids (inhibit the Oxidase enzyme, prevents oxidation) and Isoflavones (eliminates RL and prevents the growth of DNA mutations) that eliminate free radicals (RL). Quercetin (belongs to the group of flavonoids) captures and eliminates RL, facilitating the creation of endogenous antioxidants. Once the antioxidants have been characterized, a search for the types of antioxidants present in the 28 aromatic species cultivated in the IIHLD was conceived. It is concluded that the antioxidants identified in the 28 aromatic and medicinal species constitute valuable information for human health. Knowledge of the nutritional value of aromatic and medicinal plants creates a culture of their consumption in their eating habits. Consumption should be done in small doses to avoid adverse health effects, preferably consume natural antioxidants over generic ones. All species identified in the IIHLD possess natural antioxidants.